CMTM3 suppresses chordoma progress through EGFR/STAT3 regulated EMT and TP53 signaling pathway - Wanqiong Yuan (Cancer Cell International, 2021)
Abstract Background Chordomas are rare, slow-growing and locally aggressive bone sarcomas. At present, chordomas are difficult to manage due to their high recurrence rate, metastasis tendency and poor prognosis. The underlying mechanisms of chordoma tumorigenesis and progression urgently need to be explored to find the effective therapeutic targets. Our previous data demonstrates that EGFR plays important roles in chordoma development and CKLF-like MARVEL transmembrane domain containing (CMTM)3 suppresses gastric cancer metastasis by inhibiting the EGFR/STAT3/EMT signaling pathway. However, the roles and mechanism of CMTM3 in chordomas remain unknown. Methods Primary chordoma tissues and the paired adjacent non-tumor tissues were collected to examine the expression of CMTM3 by western blot. The expression of CMTM3 in chordoma cell lines was tested by Real-time PCR and western blot. CCK-8 and colony forming unit assay were performed to delineate the roles of CMTM3 in cell proliferation. Wound healing and Transwell assays were performed to assess cell migration and invasion abilities. A xenograft model in NSG mice was used to elucidate the function of CMTM3 in vivo. Signaling pathways were analyzed by western blot and IHC. RNA-seq was performed to further explore the mechanism regulated by CMTM3 in chordoma cells. Results CMTM3 expression was downregulated in chordoma tissues compared with paired normal tissues. CMTM3 suppressed proliferation, migration and invasion of chordoma cells in vitro and inhibited tumor growth in vivo. CMTM3 accelerated EGFR degradation, suppressed EGFR/STAT3/EMT signaling pathway, upregulated TP53 expression and enriched the TP53 signaling pathway in chordoma cells. Conclusions CMTM3 inhibited tumorigenesis and development of chordomas through activating the TP53 signaling pathway and suppressing the EGFR/STAT3 signaling pathway, which suppressed EMT progression. CMTM3 might be a potential therapeutic target for chordomas.